181k views
5 votes
4x-8/x^2+3x-10 = 4(x-2)/x^2+3x-10 factor the quadratic expression in the denominator of the expression.

4x-8/x^2+3x-10 = 4(x-2)/x^2+3x-10 factor the quadratic expression in the denominator-example-1

1 Answer

3 votes

Answer:

(x + 5)(x - 2)

Explanation:

Given

x² + 3x - 10 ← expression on the denominator

Consider the factors of the constant term (- 10) which sum to give the coefficient of the x- term (+ 3)

The factors are + 5 and - 2, since

5 × - 2 = - 10 and 5 - 2 = + 3, thus

x² + 3x - 10 = (x + 5)(x - 2)

User Icemelon
by
4.7k points